PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I MELALUI MEDIA BIG BOOK DI SD ISLAM TERPADU AZ-ZAHRA - Isa, Asma; Abd Hamid Isa; Yurni Rahman (Jurnal Lentera Edukasi, 2025)
This research aims to improve the beginning reading skills of class I students of SDIT Az-Zahra, Gorontalo City through the application of Big Book media. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of three meetings. The research subjects were 12 students. The instruments used included observation sheets and reading skills tests. The results of the study showed an increase in students' reading skills classically from the pre-cycle stage to the end of cycle II. At the pre-cycle stage, the student completion rate only reached 16.67% with the category of less skilled. After the implementation of the action in cycle I, the completion increased to 41.67% with a fairly skilled category. Furthermore, in cycle ll, the completion increased significantly to 91-67% with a very skilled category and had met the performance indicators set, which was 280%. Thus, there was an increase of 50% from cycle I to cycle lI. These results prove that the use of Big Book media is effective in improving the initial reading skills of grade I students of SDIT Az-Zahra, Gorontalo City.